Methods of strengthening flood-embankments = Metody wzmacniania wałów przeciwpowodziowych - Bobowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Effective flood protection is one of the most important elements connected with the management of the Oder river-basin. This article introduces and describes briefly methods and technologies applied in modernization and protection against flood embankments.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)